Educational change in a crisis: what has changed and what is here to stay in undergraduate teaching and learning in General Practice - Karen Kyne; Aileen Barrett (James Cook University, 2023)
Objectives: The aim of the study was to explore the decisions and decision-making strategies employed by academic GPs tasked with adapting the delivery of undergraduate general practice education curricula to virtual platforms during the COVID-19 pandemic and to investigate how their experiences of this adaptation might influence the development of future curricula. Methods: Approaching the study from a constructivist grounded theory (CGT) perspective, we recognised that experiences shape perception, and an individual's 'truths' are socially constructed. Nine academic GPs from three university GP departments participated in semistructured interviews conducted via Zoom©. Anonymised transcripts were iteratively analysed, generating codes, categories, and concepts using a constant comparative approach. The study was approved by the Royal College of Surgeons in Ireland (RCSI) Research Ethics Committee. Results: Participants described the transition to online delivery of the curriculum as a 'response approach'. The elimination of in-person delivery necessitated the changes rather than any strategic development process. With varying levels of experience in eLearning, participants described the need for and engagement with collaboration both internally within institutions and externally between institutions. Virtual patients were developed to replicate learning in a clinical environment. How these adaptions were evaluated by learners differed across the institutions. The value and limitations of student feedback as a driver for change differed between participants. Two institutions plan to incorporate aspects of blended learning going forward. Participants recognised the impact of limited social engagement between peers on social determinants of learning. Conclusion and implications: Prior experience in eLearning appeared to colour participants' perceptions of its value; those experienced in online delivery were inclined to recommend some level of continuation post-pandemic. We now need to consider which elements of undergraduate education can be delivered effectively online into the future. Maintaining the socio-cultural learning environment is of critical importance but must be balanced by efficient, informed and strategic educational design.